Awareness of obstetric warning signs in Ecuador: a cross-sectional study. (July 2019) - Bustamante, G.; Mantilla, B.; Cabrera-Barona, P.; Barragán, E.; Soria, S.; Quizhpe, E.; Jiménez Aguilar, A.P.; Hinojosa Trujillo, M.H.; Wang, E.; Grunauer, M.
Abstract: Objective: In Ecuador, the reported maternal death rate was 45.71 per 100, 000 live births in 2013. This may be partly due to a lack of maternal knowledge of obstetric warning signs during pregnancy, delivery and the post-partum period. This study sought to evaluate awareness of obstetric warning signs among pregnant women in relation to individual demographic and area-level socio-economic indicators. Study design: We conducted a cross-sectional analysis of data collected by Ecuador's Ministry of Health at the conclusion of a national maternal health campaign (2014–2015). A nationally representative sample of 3435 pregnant women from the nine administrative zones completed surveys regarding basic demographics and their awareness of obstetric warning signs. Methods: We defined eight obstetrical warning signs according to the literature and Ecuadorian practice that could occur during pregnancy, delivery and the post-partum period (severe headache, strong abdominal ache, bleeding or presence of malodorous secretion, rupture of the amniotic sac, high fever, abnormal presentation of the baby, decrease in baby's movements and delayed labour). A woman was considered 'aware' if she recognised at least four of the eight warning signs and stated she would seek immediate healthcare at their presentation. For each administrative zone, four socio-economic indicators (poverty, illiteracy, unemployment and subemployment) were obtained from the National Institute of Statistics and Census. Correlates of awareness of the obstetric warning signs were evaluated using hierarchical logistic models clustered by the administrative zone. Results: Nationally, 86.9% of women were 'aware' of obstetric warning signs. After adjustment for age, socio-economic indicators and clustering, indigenous participants were 59% less likely to be aware of obstetric warning signs than mestizos (odds ratio [OR] = 0.41, 95% confidence interval [CI] = 0.28–0.59). For every 1% increase in area poverty, participants had a 5% decreased likelihood of being aware of obstetric warning signs (OR = 0.95, 95% CI = 0.93–0.96), adjusting for age, ethnicity and other socio-economic indicators. The most effective source of campaign information about obstetric warning signs was personal communication with a healthcare professional, as opposed to mass media advertisements (OR = 1.90, 95% CI = 1.34–2.71). Conclusions: A majority of Ecuadorian pregnant and post-partum women are aware of obstetric warning signs. Indigenous ethnicity and area-level poverty are associated with a lack of awareness. Personal communication with a healthcare professional was the most effective source of information. These findings have implications for improvement of maternal awareness of warning signs. Highlights: Area-level poverty is associated with a lack of awareness of obstetric warning signs. Indigenous women are less likely to seek immediate care in the presence of obstetric warning signs. Health providers can more effectively communicate health information than social media tools. Social inequalities in the recognition of obstetric warning signs may lead to maternal death.